2001
DOI: 10.1590/s0004-282x2001000400002
|View full text |Cite
|
Sign up to set email alerts
|

Distant microglial and astroglial activation secondary to experimental spinal cord lesion

Abstract: This paper analysed whether glial responses following a spinal cord lesion is restricted to a scar formation close to the wound or they might be also related to widespread paracrine trophic events in the entire cord. Spinal cord hemitransection was performed in adult rats at the thoracic level. Seven days and three months later the spinal cords were removed and submitted to immunohistochemistry of glial fibrillary acidic protein (GFAP) and OX42, markers for astrocytes and microglia, as well as of basic fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
7
24
0
Order By: Relevance
“…These results are in line with previous descriptions on the central glial responses after peripheral nerve injury discussed above. It should be mentioned that glial activation does not occur only close to compromised neurons, but also it can be more widespread as recently described for small lesions in the central nervous system 12,[36][37][38] . It is possible that double crush lesion of the sciatic nerve plus local injections performed herein has also triggered some degree of astroglial reaction in the contralateral grey matter of the spinal cord, impairing demonstration of statistical differences antimerically.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…These results are in line with previous descriptions on the central glial responses after peripheral nerve injury discussed above. It should be mentioned that glial activation does not occur only close to compromised neurons, but also it can be more widespread as recently described for small lesions in the central nervous system 12,[36][37][38] . It is possible that double crush lesion of the sciatic nerve plus local injections performed herein has also triggered some degree of astroglial reaction in the contralateral grey matter of the spinal cord, impairing demonstration of statistical differences antimerically.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, SC suspension employed in this work was a source of neurotrophic factors. Moreover, a one week spinal cord lesion performed herein in order to obtain the cord extract was suffi cient to trigger a massive astroglial activation with increased level of astroglial neurotrophic factor as well 12 . However, cord extract may also possess a number of toxic substances which are released by degenerated neurons.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…If this was caused by the inflammatory reaction produced by dural suture, this inflammatory reaction may have also contributed for the structural disruption of the spinal cord at the lesion level. Accordingly, studies on acute spinal cord lesion models show that the suppression of the inflammatory response may reduce neuronal lesions (28) . The results of the present study showed that all cases submitted to neurosurgical correction presented premature labor, whereas all cases of simplified correction reached gestation term.…”
Section: A D B E C Fmentioning
confidence: 99%